Urine Specific Proteins and Alpha-1 Antitrypsin Concentrations to Assess the Severity of Lupus Nephritis - Hani Susianti; Wisnu Barlianto; Dian Sukma Hanggara; Kusworini Handono; Purwanto Adipireno; Lisyani Suromo (Research Journal of Life Science, 2017)
Background. Current biomarkers for evaluating disease activity or severity in lupus nephritis (LN) are considered to be unsatisfactory. Pathological changes in glomerular basement membrane and selectivity of electrical discharge are causing specific patterns of urine proteins excretion. Together with alpha-1 antitrypsin (AAT), they are expected to become new biomarkers to assess LN activity.Method. Seventy-one urine samples were collected from healthy controls and LN patients. Patterns of urine specific proteins were determined using column chromatography and SDS-PAGE tests, LN activity was calculated using SLEDAI-renal domain score, and AAT concentrations was measured by ELISA.Result. The majority of proteins in the control group have molecular weights of >66 kDa (88%) and 21- to 25-kDa proteins were observed only in the case group. The p values for differences in urine AAT concentration between active LN and healthy controls, inactive LN and healthy controls, and active LN and inactive LN were 0.004, 0.046, and 0.054, respectively, whereas those for urine AAT/creatinine ratio were 0.489, 0.019, and 0.915, respectively.Conclusion: There were differences in the patterns of the molecular weight of proteins and urine AAT concentrations between case group and control group. However, no such differences were identified between active and inactive LN.